Coarse graining and adsorption in bottlebrush–colloid mixtures. Issue 13 (8th March 2021) - Corsi, Pietro; González García, Álvaro; Roma, Elia; Gasperi, Tecla; Capone, Barbara
Abstract : We present a comprehensive study based on computational methods, scaling theories and self consistent field computations to predict the adsorption properties in bottlebrush/colloid mixtures. Abstract : We study the adsorption properties in bottlebrush/colloid binary mixtures by combining scaling theories, theoretical predictions, self-consistent field computations (SCFC), and molecular dynamics simulations. In particular, we focus on adsorption in the case in which an attraction is set between the two species, by analysing the solution properties for a range of interactions and the size ratio between colloids and bottlebrushes, in the case in which colloids are smaller than the macromolecules. We show that the onset of adsorption is dominated by the local properties of the adsorbing guest particle. This allows us to use the local similarity between a cylindrical bottlebrush and a spherical star polymer to predict the region of the parameter space in which the adsorption takes place. By employing simple scaling arguments, we thus extend the analytical results on the adsorption obtained for binary mixtures of star polymers/colloid nanoparticles. We then validate our predictions with molecular dynamics simulations. Moreover, by means of SCFC, we assess the adsorption-to-depletion transition of nanoparticles in polymeric bottlebrushes. Our results pave the road towards a smart rational design and coarse-graining of adsorbing/releasing systems, where an elongated shape might play an important role.